Prediction of the Main Girths of Young Female Based on 3D Point Cloud Data (Journal of Fiber Bioengineering and Informatics, 2012)
Girths of human body are significant parameters in pattern design, affecting the fitting and aestheticsof clothing. In this paper, 110 female undergraduates in Soochow University were measured by usingphotogrammetric measurement and 3D non-contact measurement system. The silhouette of human bodywas extracted by using software Matlab to obtain width and thickness. The measurements of the girthswere gotten via software Imageware based on 3D point cloud data. According to the ratio betweenthickness and width, classification of those females was carried out and the regression equation of eachcluster was obtained. The analyzed results show that the proposed non-contact measurement methodcan reduce influence of subjective factors. Regression equations can be applied to predict main girths.It will be helpful in the automatic design of garment pattern.